Electronic SOPs vs. paper - compliance with FDA CFR 21 part 11 - Turner, Gareth (Henry Stewart Talks, 2013)
Before technology, From paper to technology, EDMS development, EDMS functionality, Functionality and CFR 21, Record retention, Electronic signatures